PERANCANGAN SISTEM MONITORING DAN KONTROLING POMPA AIR BERBASIS ANDROID - Yan Mitha Djaksana; Kelvin Gunawan (SINTECH (Science and Information Technology) Journal, 2021)
Water is a necessity that is so important for every creature in the world, and the estimate of water must always be available or it is in homes, offices, public places or industry. This causes the water storage tank to play an important role in ensuring the availability of air is always there and under control. In this research, it is based on an Android-based Water Pump Monitoring and Control system with the support of IoT (Internet of Things) technology so that it makes it easier for users to monitor the amount of water in the storage tank and control the water pump to fill water into the tank, the system built is supported by the NodeMCU module. esp8266, Relay and Ultrasonic Sensor and connected to the Blynk application which functions as an application interface in monitoring and controlling the water pump. If the air has determined the specified distance, a notification will appear to immediately turn off the water pump, thus it is hoped that this system can help users see the condition of the water pump and water tank even though they are not at home